Deterioration of Chronotropic Responses and Heart Rate Recovery Indices in Men With Erectile Dysfunction. Issue 1 (20th December 2017) - Kucukdurmaz, Faruk; Acar, Gurkan; Resim, Sefa
Abstract: Introduction: Erectile dysfunction (ED) and cardiovascular (CV) diseases share common risk factors and ED has been accepted as an early manifestation of CV disease. Exercise stress testing (EST) is used to evaluate CV functions in men with ED. Low exercise workload, a slower heart rate recovery (HRR) after exercise, and inability to increase heart rate during EST (chronotropic incompetence) are independent negative predictors of adverse CV outcomes. Aim: To assess the association among EST parameters, ED, and testosterone levels. Methods: The study population consisted of 41 patients with ED and 40 controls. All participants underwent treadmill EST to assess cardiac autonomic functions. HRR indices were calculated by subtracting 1st (HRR1), 2nd (HRR2), and 3rd (HRR3) minute heart rates during the recovery period from maximal heart rate. Total exercise duration, exercise capacity and chronotropic response, and plasma testosterone levels were evaluated. Erectile functions were evaluated with the Sexual Health Inventory for Men. Patients were divided into subgroups according to severity and duration of ED. Main Outcome Measures: Mean HRR1 (30.6 ± 11.9 vs 36.9 ± 9.9; P = .01), HRR2 (44.9 ± 12.4 vs 54.9 ± 7.8; P < .001), and HRR3 (50.1 ± 11.7 vs 63.0 ± 7.9; P < .001) were significantly lower in the ED than in the control group. Total exercise duration (9.4 ± 1.9 vs 10.9 ± 1.7 minutes; P < .001), exercise capacity (12.5 ± 1.9 vs 13.6 ± 1.4 metabolic equivalents; P = .004), and chronotropic response (0.88 ± 0.1 vs 1.0 ± 0.1; P < .001) were worse in the ED group. However, we found no association between severity and duration of ED and EST parameters. In addition, serum testosterone levels were significantly correlated with HRR1 (r = 0.36, P = .02) in men with ED. Conclusion: Our data suggested that cardiac autonomic functions are impaired in patients with ED. A weak correlation between cardiac autonomic dysfunction and low testosterone levels in patients with ED was noted. However, further studies are needed to elucidate the prognostic significance and clinical implications of impaired autonomic functions and testosterone replacement therapy in patients with ED.